EFFEKTIVITAS MODEL PEMBELAJARAN HYPNOTHERAPY DALAM MENINGKATKAN ENGLISH COMMUNICATIVE COMPETENCE - Dwi Maryanti; Nursanti Dwi Yogawati (JURNAL KEBIDANAN, 2015)
Speaking one language skills or English Communicative Competence (EEC), which must be mastered in Inggris.Kelemahan language learning students in the ability to communicate in English is because (1) the low motivation of students in learning English, (2) the limited vocabulary or vocabulary controlled, (3) strategies in the face of student learning English simply by performing a given task or lecturer.This research is a quasi experimental with control group. Population and sampling in this study were all freshman courses Pharmacy academic year 2013/2014 there were 38 students. Then it will be divided into two (2) classes. Pharmaceuticals A class is a group of experimental and pharmaceutical group B is a control class. Data were analyzed using T test with confident interval of 95% and a significance level of 0.05 ..The results of the analysis of differences ECC experimental group and control group after applied learning models using hypnotherapy obtained : 0.05.athe value t: -2.210, p-value Value: 0,041 along with  Of the value can be interpreted that statistically there is a difference ECC in the experimental group or the control group after applied learning models using hypnotherapy. Conclusion: learning model using hypnotherapy effectively improve ECC.